Write right : an English handbook - Bob, Furnish (Indiana : Phi Delta Kappa Educational Foundation, 1996)
It is something nearly all of us do practically every day. No matter what walk of life you may be in, you need to communicate with other people. Writing is not only about novels and textbooks. It's also about memos, outlines, reports, instructions, and letters.
Part1. Structures of writing -- Part2. Principles of writing -- Part3. Forms of writing .
Includes bibliographical references and index.
Keywords: ENGLISH LANGUAGE COMPOSITION